Changes in Quality of Life in Elementary School Children-The Health Oriented Pedagogical Project (HOPP) - Per Morten Fredriksen; Helene Kristine Olsen; Trine Johansen Meza (MDPI AG, 2019)
Abstract: Background: Quality of life (QoL) studies may provide information of change in health status in the population. Few studies have followed up previous cross-sectional studies to investigate any change in the QoL status of healthy children. The aim of the current study is to compare QoL in children 6–12 years old in two large cross-sectional studies of healthy children completed a decade apart. Methods: In the current study children and parents from nine elementary schools (n = 2816) were included in a cross-sectional study investigating children’s QoL. Using the Life Quality in Children and Adolescents (ILC), completed by both children and parents, the global QoL-score was estimated for 2297 children and 1639 parental reports. These results were compared to a similar study performed in 2004. The scores from both studies were divided into categories of below average, average and above average QoL. The percentage change of QoL between the two studies is presented. Results: Our results show that parents report that more children have below and above average QoL in 2015 compared to 2004. In contrast, more children scored in the average and above average QoL category in 2015 than in 2004. Conclusion: Parents reported lower QoL and children higher QoL in 2015 compared to 2004.